A state-of-the-art review of an optimal sensor placement for contaminant warning system in a water distribution network. Issue 10 (26th November 2018) - Adedoja, Oluwaseye S.; Hamam, Yskandar; Khalaf, Baset; Sadiku, Rotimi
ABSTRACT: Protection of water distribution networks (WDNs) is at the forefront because of the negative implications of the use of the contaminated water on the public health. In order to safeguard the water distribution networks from accidental and intentional attacks, a water quality sensor should be installed across the network. Remarkably, the budget constraints to procure and maintain sensors have limited the number of sensors deployed in networks. These constraints make the optimal sensor placement receive notable attention. Over time, researchers have devised various methodologies to tackle sensor placement in a water distribution network. Investigations have shown that each of the methodologies has a research gap which must be addressed. In this work, a state-of-the-art review of optimal sensor placement in a water distribution network is presented. The review results show technical challenges, possible solutions, and future research directions in this domain.